2008
DOI: 10.17221/1942-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Model of septic shock induced by live E. coli (O18) in a laboratory rat

Abstract: ABSTRACT:This study was concerned with the development of induced septic shock in a laboratory rat using a series of measurements including body temperature, heart and respiratory rates, haematocrit value, red and white blood cell counts, differential leukocyte count, haemoglobin value, glycaemia, analysis of arterial blood gases, and serum levels of interleukin 6 (IL-6) during the first five hours. A total of 12 specific pathogen free (SPF) laboratory rats were used for the study. Septic shock was induced und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…3. The level of Na + has not changed significantly inconsistent with a report by Dembovska et al (2008) who found that no significant difference in the levels of calcium, sodium, and potassium in an LPS-induced inflammation.…”
Section: Discussioncontrasting
confidence: 87%
“…3. The level of Na + has not changed significantly inconsistent with a report by Dembovska et al (2008) who found that no significant difference in the levels of calcium, sodium, and potassium in an LPS-induced inflammation.…”
Section: Discussioncontrasting
confidence: 87%
“…Bacterial endotoxin can have a bad impact on the cellular functions of the liver, which plays an important role in glucose homeostasis [34]. In our study, E.coli infected rats showed a significant increase in blood glucose levels all over the experiment compared to the control group, which may be attributed to severe hepatic dysfunction and the elevated ratio between corticosteroids and insulin-induced by E.coli that affect hepatic glucose metabolism and altered glucose homeostasis [36,37].…”
Section: Discussionmentioning
confidence: 58%